ROLES OF HUMAN RESOURCE INFORMATION SYSTEM (HRIS) ON EMPLOYEES’ PERFORMANCE AT SEPLAT ENERGY, LAGOS - Ayodele, Tomisin; Andow, Helen; Zwingina, Christy (African Journal of Social and Behavioural Sciences, 2025)
The need for Human Resource Information System (HRIS) in large and complex organizations is necessitated by a huge number of employees with diverse professional skills assigned to various organizations’ units that require smart management. Likewise, organizations that are geographically dispersed require HRIS to manage information and human resources from multiple locations. The study evaluates the effect of the human resource information system (HRIS) on the employees’ performance in Seplat Energy, Lagos. The study constitutes the entire population of employees in Seplat Energy, which amounts to 551. A sample of 226 was determined using the Krejcie and Morgan (1970) table. The study used various statistical tools such as descriptive statistics, correlation analysis, and multiple regression to test the hypotheses used in the study. The research revealed and concluded that the human resource information system has a positive and significant effect on the performance of employees in Seplat Energy. Specifically, database management and attendance management have significant and positive effects; the study therefore recommended that Seplat Energy should ensure that it directs resources towards database management and attendance management in order to maximize the performance of employees in the organization.